2018
DOI: 10.1021/acs.accounts.8b00225
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ethylene/Polar Vinyl Monomer Copolymerizations Using Ni and Pd α-Diimine Catalysts

Abstract: The most ubiquitous polymer, polyethylene (PE), is produced either through a radical-initiated process or, more commonly, through a coordination/insertion process employing early transition metal catalysts, particularly titanium- and chromium-based systems. These oxophilic early metal catalysts are not functional-group-tolerant and thus cannot be used to synthesize copolymers of ethylene and polar vinyl monomers such as alkyl acrylates and vinyl acetate. Such PE copolymers have enhanced properties relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
257
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(266 citation statements)
references
References 40 publications
3
257
0
6
Order By: Relevance
“…In both cases, olefin coordination leads to a lowering of the π *(M−C) orbital, leading to a deshielding for d 0 systems, but to a shielding for d 8 systems. Notably, the inverse polarization of the methyl group in d 8 and d 0 systems entails a fundamentally different reactivity, as evidenced in the opposing regioselectivities in propylene insertion, or the reactivity and regioselectivity observed in the reaction of acrylates with d 8 systems …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, olefin coordination leads to a lowering of the π *(M−C) orbital, leading to a deshielding for d 0 systems, but to a shielding for d 8 systems. Notably, the inverse polarization of the methyl group in d 8 and d 0 systems entails a fundamentally different reactivity, as evidenced in the opposing regioselectivities in propylene insertion, or the reactivity and regioselectivity observed in the reaction of acrylates with d 8 systems …”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25][26] The functional group tolerance of these d 8 complexes has allowed for the copolymerization of unfunctionalized α-olefins with polar vinyl monomers such as methyl acrylate. [27][28][29][30][31] Furthermore, it is also noteworthy that insertion of propylene and methyl acrylate preferentially occurs in a 2,1-fashion, [21,28,32] that is opposite to the observed regioselectivity for d 0 systems and is often followed by isomerization through chain walking. [33] In analogy to d 0 catalysts, CÀ H bond activation has also been observed for d 8 systems: Pd(II) polymerization catalysts are prone to deactivation through intramolecular ligand CÀ H activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd‐diimine complexes were reported to catalyze polymerization of ethylene, α‐olefins, and cycloolefins to give the corresponding polymers . The polymer growth is accompanied by rapid olefin migration, named as chain walking, which is caused by repetitive β‐hydrogen elimination and reinsertion of the vinyl group‐terminated polymer molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, fundamental polar monomers with polar functional groups directly attached to the double bond are industrially more relevant and are more difficult to handle during copolymerization reactions.T he seminal works by Brookhart et al in 1996 demonstrated the copolymerization of ethylene with some acrylates and vinyl ketone comonomers. [17] After two decades of extensive research, [18][19][20][21] the Brookhart-type catalysts were only suitable for af ew other fundamental polar monomers. [22][23][24][25] In 2002, Drent and co-workers reported another major breakthrough in this field.…”
mentioning
confidence: 99%